Families of Children with Disabilities: Challenges and Coping Strategies in Some Selected Towns of Arsi Zone - Disasa, Begashaw (Journal of disability & religion, 2023)
The purpose of this study was to investigate the common challenges that families faced and the different coping strategies they employed in bringing up their children with disability in some selected towns of Arsi Zone. Arsi zone is found in central Ethiopia located in the Oromia region state about 175 kilometers from Addis Ababa. Researcher employed a qualitative research design. Ten interviews and three focus group discussions were conducted with parents of children with disabilities who send their children to Arsi zone government schools that have special classes for such children. A purposive sampling method was used to recruit the study participants. A digital recorder was used to record all the interviews and focus group discussions. The results indicate that parents of children with disabilities experience common challenges including objective challenges (problems associated with time constraint, financial burden, impact on day to day activities, lack of social support) and subjective challenges (Feeling of consistent chronic sorrow, less social interaction). They described experiences of their positive perceptions in raising their children and discuss coping strategies that have been most helpful to them such as beliefs in God, evaluating child’s progress, service provision and experience sharing. They also indicated their strong needs about vocational training for their children.